Know how to handle employee protests, refusals to engage in work. Issue 8 (26th March 2019) - Porter, Michael; Burris, Erin
Abstract : Silent Sam is a 105‐year‐old statue of a Confederate soldier on the University of North Carolina campus. Protesters have toppled it, and UNC's leadership has had to address the campus unrest concerning the statue's placement, which is governed in part by North Carolina state law.